1992
DOI: 10.1073/pnas.89.20.9454
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle-dependent localization of casein kinase I to mitotic spindles.

Abstract: Casein kinase I (CKI) is a class of protein kinases ubiquitous to all eukaryotic cells. Recently, cDNA clones encoding several bovine CKI isoforms have been sequenced that show high sequence identity to the 1IRR25 gene product of the budding yeast Saccharomyces cerevisiae; MRRM is required for normal cellular growth, nuclear segreption, DNA repair, and melosis. We have raised polyclonal antibodies to a human erythroid 34-kDa CMI and have sequenced a portion of this kinase. The amino acid sequence identifies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 42 publications
5
90
2
Order By: Relevance
“…Ca 2 /calmodulin kinases II [40] MT stability? Casein kinase I-K [41] Casein kinase II [42] Fyn [43] Signaling in T lymphocytes. Phosphoinositide 3-kinase [44] LK6 [45] PKC-d [46] Phosphatases d :…”
Section: Polo Kinases and Spindle Formationmentioning
confidence: 99%
“…Ca 2 /calmodulin kinases II [40] MT stability? Casein kinase I-K [41] Casein kinase II [42] Fyn [43] Signaling in T lymphocytes. Phosphoinositide 3-kinase [44] LK6 [45] PKC-d [46] Phosphatases d :…”
Section: Polo Kinases and Spindle Formationmentioning
confidence: 99%
“…For example, DMCK1 (the homologue of CK1a in D. melanogaster), is activated following DNA damage and relocates to the nucleus (Santos et al, 1996), while mammalian CK1a is located at the mitotic spindle and the Oncogene (2000) 19, 5303 ± 5313 ã 2000 Macmillan Publishers Ltd All rights reserved 0950 ± 9232/00 $15.00 www.nature.com/onc *Correspondence: U Knippschildcentrosomes in both mouse ®broblasts and oocytes (Brockman et al, 1992;Gross et al, 1997). Recently we showed that CK1d is recruited to the mitotic spindle and the centrosomes following treatment with etoposide or g-irradiation in rodent cells (Behrend et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian cells, CK1α was first reported to localize to vesicular cytolic structures and centrosome in interphase cells, and then associated with spindles in mitosis [9]; CK1δ was localized to centrosomes, co-localized with γ-tubulin and was associated with the mitotic spindles under DNA damage; and CK1ε was concentrated at centrosomes [31]. Cell treated with IC261 caused mitotic spindle defects and cell cycle arrest.…”
Section: The Role Of Ck1 Isoforms In Meiosismentioning
confidence: 99%
“…The CK1 isoforms was found to play an important role in cancer progression in different types of tumors [28]. The localization of CKlα in the mitosis was researched by immunofluorescent studies using mouse fibroblasts and CHO cells [9]. In interphase cells, CK1α was localized to vesicular cytosolic structures.…”
Section: Expression and Subcellular Localization Of Ck1mentioning
confidence: 99%
See 1 more Smart Citation